The Influence of Perceived Ethicality and Electronic Word of Mouth (E-WOM) on E-Loyalty through Customer E-Trust Wardah Compact Powder in Cimahi City - Salma Aziizu; Hariyadi Triwahyu Putra (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the digital cosmetics industry increases competition between brands, so companies need to understand the factors that shape customer e-loyalty. The decline in loyalty in Wardah solid powder products prompted this study to analyze the influence of perceived ethicality and electronic word of mouth (e-WOM) on e-loyalty through e-trust as a mediating variable in Wardah solid powder customers in Cimahi City. The study used a quantitative approach with a survey method of 120 respondents selected using convenience sampling. Data were analyzed using multiple regression and mediation tests. The results of the study show that perceived ethicality and e-WOM have a positive effect on e-trust, and e-trust has a positive effect on e-loyalty. E-trust is able to mediate the influence of perceived ethicality on e-loyalty, but does not mediate the influence of e-WOM on e-loyalty. This study concludes that increasing the perception of brand ethics and the quality of digital communication can strengthen customer trust and loyalty. The results of the study provide recommendations for PT Paragon Technology and Innovation to increase e-loyalty through strengthening ethical perception, e-WOM quality, e-trust, product quality consistency, privacy protection, clarity of information, complaint handling, and encouraging positive reviews on e-commerce platforms.